Mass-produced food: the rise and fall of the promise of health and safety - Chad M. Baum (Max Planck Institute of Economics, 2013)
The greater awareness of the negative environmental and health-related externalities of the large-scale food industry is directly responsible for the diminished confidence of the quality of its products. Using the multi-level perspective on socio-technical transitions (Geels, 2004; 2010), I argue that the initial impetus for the emergence of mass production was the presence of threats to health and safety in the broader societal context. Rather than simply serving economic considerations, the scale and scientific expertise of mass production functioned as a credible signal due to its relationship to these threats. The declining health and safety of the food industry represents, however, a consequence of the changing relationship of scale and quality due to the emergence of new threats to health and safety. Scale as a signal of credibility is no longer sufficient to guarantee these qualities, however. Absent the incentives to undertake costly investments in quality production, the criteria of productivity and efficiency become duly emphasized to the detriment of health and safety. Hence, the continued emphasis on scale now represents a limitation to improving health and safety. Instead, further quality innovation demands the development of a costly signal appropriate to the extant social context.
Keywords: 330; socio-technical transitions; health and safety of the food industry; mass production; credibility